2006
DOI: 10.1021/ic052161f
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Oxidation of Phosphines Employing Water as the Oxygen Atom Source and Tris(benzene-1,2-dithiolate)molybdenum(VI) as the Oxidant. A Functional Molybdenum Hydroxylase Analogue System

Abstract: The kinetics of the reaction of Mo(VI)(S2C6H4)3 with organic phosphines to produce the anionic Mo(V) complex, Mo(V)(S2C6H4)3-, and phosphine oxide have been investigated. Reaction rates, monitored by UV-vis stopped-flow spectrophotometry, were studied in THF/H2O media as a function of the concentration of phosphine, molybdenum complex, pH, and water concentration. The reaction exhibits pH-dependent phosphine saturation kinetics and is first-order in complex concentration. The water concentration strongly enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Therefore, the metal center at Mo and W tris(dithiolenes) is described as a V state rather than a VI oxidation state, preventing coordination sphere expansion. On the other hand, the cleavage of the W-S bond is entirely consistent with the OAT reactivity exhibited by these complexes toward oxo acceptors as organic phosphines [48] or sulfite in aqueous media [47].…”
Section: Reduction Of Tungsten Tris(dithiolenes) In Aqueous Mediasupporting
confidence: 72%
See 1 more Smart Citation
“…Therefore, the metal center at Mo and W tris(dithiolenes) is described as a V state rather than a VI oxidation state, preventing coordination sphere expansion. On the other hand, the cleavage of the W-S bond is entirely consistent with the OAT reactivity exhibited by these complexes toward oxo acceptors as organic phosphines [48] or sulfite in aqueous media [47].…”
Section: Reduction Of Tungsten Tris(dithiolenes) In Aqueous Mediasupporting
confidence: 72%
“…However, very recently, we have shown that the reduction of these complexes by using some chemical reductants in the presence of water cannot be explained by simple outer-sphere electron transfer reactions. For instance, [Mo(S 2 C 6 H 4 ) 3 ] oxidizes sulfite to sulfate [47] and organic phosphines to their corresponding oxides [48], through a mechanism involving probably the initial coordination of water to the molybdenum center, followed by the oxygen atom transfer (OAT) to the substrate to give its oxidized form.…”
Section: Introductionmentioning
confidence: 99%
“…The nucleophilic attack of H 2 O or OH – toward the phosphorus atom of R 3 P •+ generates phosphoranyl radical species (R 3 P • –OH), which further undergo several radical chain processes (including O 2 •– and H 2 O 2 ) and subsequently gives the R 3 PO as the final stable product (eq 2 in Scheme B) . Previous reports of unusual reducing properties of R 3 P by utilizing H 2 O or OH – as a source of oxygen rather than O 2 further supports this mechanism. Luc •+ then react with R 3 P • –OH radicals to generate the excited N -methylacridone (emitter) and R 3 PO.…”
Section: Resultsmentioning
confidence: 58%
“…•− and H 2 O 2 ) and subsequently gives the R 3 P O as the final stable product (eq 2 in Scheme 1B). 52 Previous reports of unusual reducing properties of R 3 P by utilizing H 2 O or OH − as a source of oxygen rather than O 2 54 further supports this mechanism. Luc •+ then react with R 3 P • −OH radicals to generate the excited N-methylacridone (emitter) and R 3 PO.…”
Section: ■ Experimental Sectionmentioning
confidence: 83%
“…Perhaps the most amazing aspect of tris-dithiolato chemistry is the reactivity toward water which is not expected to be relevant due to the stability of the Mo–S bond and the electronic structure of tris-dithiolato complexes. However, oxygen exchange between water and phosphines or sulfite mediated by [Mo­(C 6 H 4 S 2 ) 3 ] has been reported. , The mechanism is supposed to involve initial coordination of water to the molybdenum–dithiolato species . The oxo-transfer activity of neutral tris-dithiolato complexes is difficult to understand based only on the d 1 , or more probably d 2 , electronic structure of metal center, which would make the postulated initial formation of a heptacoordinated aquo tris-dithiolato intermediate an unlikely event .…”
Section: Introductionmentioning
confidence: 99%